Saul the Sadducee?: A Rabbinical Thought Experiment - Isbell, Charles D. (Socio-historical examination of religion and ministry, 2019)
In keeping with talmudic tradition, this article presents a rabbinical thought experiment that questions the authenticity—indeed the very historicity—of the Apostle Paul’s Pharisaic Jewish background. By examining current interpretations of Saul’s Damascus road conversion, as well as Lukan and Pauline accounts in the New Testament, it becomes evident that there exists a striking disparity between Paul and other first century Pharisees, particularly since he took far too many liberties with his beliefs and behaviors (pre- and post-conversion) that would have set him apart from his Pharisaic contemporaries. Moreover, Luke (a non-Jew writing in a post-Sadducean world) was both an unreliable biographer and yet the primary source for claiming Paul was a Pharisee. Thus, from a Jewish perspective, it is thought-provoking to ask whether the idea of Paul as originally a Sadducee best explains these disparities. Ultimately, the thesis of this article is that interpreters should not view Paul as having followed the standard path to becoming an authentic Pharisee. In fact, Paul’s radical revision of prevailing Pharisaic exegesis suggests he was likely never a Pharisee or, at the very least, not a consistent Pharisee in the tradition of Gamaliel. The purpose of this article is to trace just how modern scholarship would change if Pauline scholars presumed that Paul was, in fact, a Sadducee instead of a Pharisee. Undoubtedly, the consequence would suggest that both Paul and Luke were world-class (albeit opportunistic) rhetoricians who used Pharisaic imagery solely to add credibility to Paul’s image and his emerging influence on the primitive church.